Realizing the Potential of Islamic Finance - Mohieldin, Mahmoud (World Bank, Washington, DC, 2012)
Islamic finance has been growing rapidly in recent years. Motivated by a heightened interest in financial instruments that emphasize risk sharing, it has been attracting greater attention in the wake of the recent financial crisis. This class of instruments appears to have avoided many of the most severe consequences of the crisis. Several features underpin the expansion and performance of Islamic finance. Addressing key regulatory and governance issues will be essential for Islamic finance to achieve its full potential. Several multilateral development institutions, including the World Bank, have longstanding programs to support the development of the industry and have used Islamic instruments, to varying extents, to tap capital markets. In the coming years, Islamic finance could account for a substantial share of financial services in several countries, meeting the preferences of significant numbers of people, enhancing financial inclusion and intermediation, and contributing more broadly to financial stability and development.